Folklore on Kayori: An Oral Tradition about Natural Disasters in Central Sulawesi - Nole, Otniel Aurelius (Institut Seni Indonesia Denpasar, 2024)
The characteristics of Indonesian society are firmly attached to the image of expressing language orally, which has been done since long ago and has survived until now. Folk beliefs and imagination are the main essences of cultured human life when creating stories. Although the current situation signifies a modern life, the researcher argued that folklore is an oral tradition still relevant to life’s context substantially and functionally, as on kayori from Central Sulawesi. This research aimed to revitalise kayori as folklore in Central Sulawesi, an oral tradition about natural disasters. The researcher generated knowledge in this research qualitatively as a method that included a literature review study. The researcher collected and used reference sources related to the variables of this study. The research showed that kayoriis a folklore that affirms oral tradition as an art to express the function of learning and remembering the messages in poems and sounds. The messages of kayori have implications for practical actions for the community regarding natural disaster mitigation related to disaster policy, ethics, religiosity, and ecological values. In the end, the verbal art of kayoriremained a part of the futuristic world because it provided knowledge on humanitarian and environmental aspects related to natural disasters in the contemporary era.